Pathways to low carbon development for Vietnam. (Metro Manila, Philippines Asian Development Bank, 2017)
This study assesses how Vietnam green growth objectives can be achieved through a detailed modeling approach that draws on extensive national stakeholder input to ensure alignment with sector plans and strategies.
Keywords: Climatic changes -- Cost effectiveness; Climatic changes -- Government policy; Electronic books